Flora bromeliologica del Estado de Guerrero, Mexico: riqueza y distribucion - Pulido-Esparza, M.A.=700 1 Lopez-Ferrari, A.R.; Espejo-Serna, A.
(En, Es)
ilus., 47 ref.
Keywords: FLORA; BROMELACEAE; VARIEDADES NATURALIZADAS; COMPOSICION BOTANICA; DISTRIBUCION GEOGRAFICA; MEXICO